2007
DOI: 10.1074/jbc.m609822200
|View full text |Cite
|
Sign up to set email alerts
|

Translational Control of Glial Glutamate Transporter EAAT2 Expression

Abstract: Glutamate is the major excitatory neurotransmitter in the central nervous system. Its activity is carefully modulated in the synaptic cleft by glutamate transporters. The glial glutamate transporter EAAT2 is the main mediator of glutamate clearance. Reduced EAAT2 function could lead to accumulation of extracellular glutamate, resulting in a form of cell death known as excitotoxicity. In amyotrophic lateral sclerosis and Alzheimer disease, EAAT2 protein levels are significantly decreased in affected areas. EAAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 64 publications
3
71
1
Order By: Relevance
“…Recent work has demonstrated that there are variants with long 5 0 -UTRs that are regulated at the translational level. 38 In this study, the transcripts with the longer 5 0 -UTRs were regulated by corticosterone, retinol and several Upstream open reading frames (ORFs), which may be translated or inhibit translation of the main protein product, are present in some of these 5 0 -UTRs. 34,36 Variants that encode upstream ORFs (such as the molecules annotated as HBGTIIB and HBGTIIC) appear to be less abundant than those that do not encode upstream ORFs.…”
Section: Evidence For An Extended Glt1b Transcriptmentioning
confidence: 86%
See 2 more Smart Citations
“…Recent work has demonstrated that there are variants with long 5 0 -UTRs that are regulated at the translational level. 38 In this study, the transcripts with the longer 5 0 -UTRs were regulated by corticosterone, retinol and several Upstream open reading frames (ORFs), which may be translated or inhibit translation of the main protein product, are present in some of these 5 0 -UTRs. 34,36 Variants that encode upstream ORFs (such as the molecules annotated as HBGTIIB and HBGTIIC) appear to be less abundant than those that do not encode upstream ORFs.…”
Section: Evidence For An Extended Glt1b Transcriptmentioning
confidence: 86%
“…GLT1 expression is also regulated by glucocorticoids including corticosterone and the synthetic molecule dexamethasone. 38,84,85 Corticosterone was found to regulate translation of GLT1 isoforms with longer 5 0 -UTRs, but not to affect transcription or protein stability. 38 This molecule led to a dosedependent increase in GLT1 protein levels in cultured astrocytes, further supporting the notion that isoforms of GLT1 are differentially regulated in response to stress.…”
Section: Mood and Anxiety Disordersmentioning
confidence: 96%
See 1 more Smart Citation
“…Cell Surface Biotinylation-Proteins on the plasma membrane were labeled by biotinylation as described previously (19). Briefly, cells were incubated with 1 mg/ml EZ-Link Sulfo-NHS-SS-Biotin in PBS buffer (137 mM NaCl, 2.7 mM KCl, 10.1 mM Na 2 HPO 4 , 1.8 mM KH 2 PO 4 , pH 7.4, 100 M CaCl 2 , and 1 mM MgCl 2 ) for 30 min at 4°C.…”
Section: N48kmentioning
confidence: 99%
“…A small 11-amino acid fragment of the fulllength peptide, Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), is a convenient alternative in Alzheimer's disease investigations as the peptide mimics several toxicological and oxidative stress properties of the native full-length peptide 4,18,19 . Recently, our group demonstrated that treatment of mixed cell cultures with 10 µM Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) for 12 h and 24 h reduces SAT1 protein level as demonstrated by immunocytochemical and quantitative immunoreactivity analysis 20 .…”
Section: Introductionmentioning
confidence: 99%